The role of thyroid stimulating hormone level as a predictive factor for advance stage thyroid carcinoma - Bambang Udji Djoko Rianto; Anton Sony Wibowo; Camelia Herdini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Thyroid stimulating hormone (TSH) is a cancer growth stimulus factor that have effect on the progression of thyroid carcinoma, common neck head malignancy. This hormonelevel has diagnostic value and can assist in the diagnosis, staging and management of the thyroid carcinoma.This study aimed to investigatethe role of TSH level as a predictor of advance stage thyroid carcinoma. This was case-control study involvingthyroid enlargement subjects who underwent thyroidectomy at Dr. Sardjito General Hospital, Yogyakartafrom 2015 to 2017. Cancer staging examination using AJCC 2102and TSH levels examination were conducted before underwent thyroidectomy.The inclusion criteria for case group were advanced stage(stage III and IV), while for control group wereearly-stage of thyroid carcinoma (stage I and II). The exclusion criteria for both case and control groups were 1) suffering from thyroid hormone disorders requiring therapy before thyroidectomy, 2) receiving thyroid suppression therapy prior to thyroidectomy. Sixty-six post thyroidectomy patients were involved in this study. The patients were divided into case and control groups consisted of 33 patients in each group. Based on receiver operating characteristic curve, the cut of point 1.27 mIU/L for TSH was obtained with sensitivity of 72.7% and specificity of 78.8%. There was statistically significant difference TSH levelsbetween early stage thyroid carcinoma and late stage thyroid carcinoma(p = 0.001;OR: 9.9;95% CI: 3.19-30.15).It can be concluded that TSHlevels ≥ 1.27mIU/L as predictor of advance stage thyroid carcinoma.